Isolation and Molecular Characterization of Thraustochytrium Strain Isolated from Antarctic Peninsula and Its Biotechnological Potential in the Production of Fatty Acids - Tello-Reyes, M (Elsevier Editora Ltda, 2017)
Thraustochytrids are unicellular protists belonging to the Labyrinthulomycetes class, which are characterized by the presence of a high lipid content that could replace conventional fatty acids. They show a wide geographic distribution, however their diversity in the Antarctic Region is rather scarce. The analysis based on the complete sequence of 18S rRNA gene showed that strain 34-2 belongs to the species Thraustochytrium kinnei, with 99% identity. The total lipid profile shows a wide range of saturated fatty acids with abundance of palmitic acid (16:0), showing a range of 16.1–19.7%. On the other hand, long-chain polyunsaturated fatty acids, mainly docosahexaenoic acid and eicosapentaenoic acid are present in a range of 24–48% and 6.1–9.3%, respectively. All factors analyzed in cells (biomass, carbon consumption and lipid content) changed with variations of culture temperature (10 °C and 25 °C). The growth in glucose at a temperature of 10 °C presented the most favorable conditions to produce omega-3fatty acid. This research provides the identification and characterization of a Thraustochytrids strain, with a total lipid content that presents potential applications in the production of nutritional supplements and as well biofuels. © 2017 Sociedade Brasileira de Microbiologia
Keywords: Thraustochytrids; Antarctic; Docosahexaenoic acid; Eicosapentaenoic acid; Temperature